Complete secretary's handbook - Doris, Lillian; Miller, Besse May (New Jersey : Prentice-Hall, 1970)
With the many changes in secretarial practices that have taken place in recent years, today's efficient secretary needs the latest authentic information pertaining to her position at her finger tips. The Complete Secretary's Handbook has now been again completely revised to give this service and includes the most modern and streamlined practices for those who want to make the most of a secretary's job potentials.
Part I. Techniques for General Secretarial Duties -- Part II. How to Write Good Letters -- Part III. How to Write Correctly -- Part IV. How to Handle Records and Correspondence for the Executive's Personal matters -- Part V. The Secretary's Handy Information Guide.
Includes index.
Keywords: OFFICE PRACTICE -- HANDBOOKS, MANUALS, ETC